The Influence Of The Problem-Based Learning Model on Social Studies Learning Outcomes Riviewerd from the Geographic Location of Fourth Grade Students in Ledokombo II Cluster - Apriani, Luh; Lasmawan, Wayan; Sanjaya, Dewa; Suastika, Nengah; Wapa, Andi (International Conference on Elementary Education, 2025)
This study aims to examine the effect of the Problem-Based Learning (PBL) model on students’ social studies learning outcomes, reviewed from their geographic location. A quasi experimental posttest-only control group design was used. The population consisted of 190 fourth-grade students in the Ledokombo II cluster, and 110 students were selected through cluster random sampling. The sample was divided into two experimental and two control classes. Data were analyzed using two way ANOVA. The results show that: (1) PBL had a significantly higher impact on learning outcomes compared to conventional teaching (F = 22.284 > Ftable = 3.93), (2) there was a significant interactionbetween learning model and geographic location (F = 66.428 > Ftable = 3.97), (3) urban students achieved significantly better results in PBL classes than in conventional classes, and (4) rural students also showed significant differences, although lower than urban groups. These findings indicate that PBL is an effective learning model across contexts, yet geographic disparities influence the magnitude of its effectiveness